Lipoic Acid Treatment after Brain Injury: Study of the Glial Reaction - Brenda Rocamonde; Sara Paradells; Carlos Barcia; Angeles Garcia Esparza; José Miguel Soria (Clinical and Developmental Immunology)
After trauma brain injury, oxidative substances released to the medium provoke an enlargement of the initial lesion, increasing glial cell activation and, occasionally, an influx of immune cells into the central nervous system, developing the secondary damage. In response to these stimuli, microglia are activated to perform upregulation of intracellular enzymes and cell surface markers to propagate the immune response and phagocytosis of cellular debris. The phagocytosis of debris and dead cells is essential to limit the inflammatory reaction and potentially prevent extension of the damage to noninjured regions. Lipoic acid has been reported as a neuroprotectant by acting as an antioxidant and anti-inflammatory agent. Furthermore, angiogenic effect promoted by lipoic acid has been recently shown by our group as a crucial process for neural regeneration after brain injury. In this work, we focus our attention on the lipoic acid effect on astroglial and microglial response after brain injury.